“The Poetics of Discourse and the Aesthetics of Imagery in the Poetry Collection ‘What the Barefoot Heart Sees in the Age of Shoes’ by Ayach Yahiaoui.” - Al-Arabi, Abdelkader (El Omda in Linguistics and Discourse Analysis, 2021)
Abstract : In life poetry is rare to spot on , albeit many try to apply many ways to make it in a casual manner but it cannot count as such when it is so simple as well as far from what we can call “ poetry “ , and only among few can grasp its true meaning , one of those is “ Ayach Yahyaoui “ Keywords:  poetry  meaning  casual  simple